ChemInform Abstract: Palladium‐Catalyzed Formation of C=C Bonds: A Regioselective Strategy for the Synthesis of 2‐Vinylfurans by 1, 2‐H Shift of Palladium—Carbene Complexes. Issue 38 (30th August 2013) - Zhan, Haiying; Lin, Xiulian; Qiu, Yanying; Du, Zuodong; Li, Peixian; Li, Yongjian; Cao, Hua
Abstract The authors present a new one‐pot cyclization reaction to the corresponding furan derivatives which proceeds under mild conditions.